Future changes in environmental stressors for the seamount chains of the Southeast Pacific - Hammond, M. L.; Ramos, M.; Gallardo, M. A.; Zhai, D.; Flores, E. A.; Gaymer, C. F.; Sellanes, J.; Luna-Jorquera, G. (Frontiers in Marine Science, 2025)
The submarine seamount chains of Nazca and Salas & Gómez in the Southeast Pacific are areas of high levels of both biodiversity and endemism. The intersection of both ridges is strongly influenced by the Eastern Boundary Upwelling System of the Southeast Pacific and its associated oxygen minimum zone (OMZ). The isolation of individual seamounts and their fragile ecosystems make them extremely vulnerable to any changes in physical and biogeochemical conditions. Here we assess how a number of key physical and biogeochemical variables are projected to change in two climate scenarios using a statistical approach known as quantile regression. This allows the assessment of trends in medians as well as ranges and extremes. Trends in medians show consistent patterns of temperature increase and pH decrease over the entire range of the seamount chains (and entire Southeast Pacific region). Chlorophyll-a appears to show an increase over the majority of the range of the seamounts except at the coast where it decreases. However, the individual seamount chains show contrasting changes for other variables, with the Nazca ridge showing increased oxygen alongside decreasing nutrient levels indicative of decreased upwelling despite contrasting changes in wind stress curl and stratification. Conversely, the Salas & Gómez ridge is projected to see a reduction in oxygen and increased nutrient levels. Alongside these broader patterns in medians, the trends in ranges and extremes are highly variable spatially and less consistent between variables and scenarios. These contrasting changes will provide both advantages and disadvantages depending on the specific species and location of the seamount of interest. These changes present the importance of classifying the desired ranges of the species within these seamount chains and the potentially complex nature of the conservation of these unique but isolated ecosystems.